(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2021)
The demand for nuclear fuel for research reactors is increasing worldwide. However, some nuclear fuel factories have small production volumes. There is a gap in the literature regarding how to expand capacity of those facilities in a safe and reliable way. Thus, the purpose of this work is to propose and validate a conceptual model to increase the production capacity of these factories. We addressed factories that produce plate-type fuel elements loaded with LEU U3Si2-Al, which are typically used in nuclear research reactors. We collected data from a real nuclear fuel plant and applied the model to that data, i.e., we set up a case study. We developed two different strategies for the use of the model, thus generating several production scenarios. Each scenario is an experiment of the different possibilities to enlarge the capacity. We applied discrete events simulation in order to cover all production scenarios. Our tests indicated significant increases in productive capacity, thus showing that the model has fully achieved its proposed objective. One of the main conclusions that we point out is the model’s effectiveness. That effectiveness was demonstrated by using the model in two different strategies and obtaining increases in capacity with both of them.